Salivary gland cancer: ESMO-European Reference Network on Rare Adult Solid Cancers (EURACAN) Clinical Practice Guideline for diagnosis, treatment and follow-up - van Herpen, C; Vander Poorten, V; Skalova, A; Terhaard, C; Maroldi, R; van Engen, A; Baujat, B; Locati, L D; Jensen, A D; Smeele, L; Hardillo, J; Martineau, V Costes; et al. (ESMO open, 2022)
• This ESMO–EURACAN Clinical Practice Guideline provides key recommendations for managing salivary gland cancer. • The guideline covers clinical and pathological diagnosis, staging and risk assessment, treatment and follow-up. • Treatment algorithms for parotid, submandibular, sublingual and minor salivary gland cancer are provided. • The author group encompasses a multidisciplinary group of experts from different institutions and countries in Europe. • Recommendations are based on available scientific data and the authors’ collective expert opinion.
Keywords: treatment; ESMO–EURACAN Clinical Practice Guideline; Salivary Gland Neoplasms; Adult; dospělí; salivary gland cancer; Humans; Follow-Up Studies; follow-up; lidé; Europe; diagnosis; Evropa; následné studie; lékařská onkologie; nádory slinných žláz; Medical Oncology